2015
DOI: 10.1038/ncb3165
|View full text |Cite
|
Sign up to set email alerts
|

ATP synthase promotes germ cell differentiation independent of oxidative phosphorylation

Abstract: The differentiation of stem cells is a tightly regulated process essential for animal development and tissue homeostasis. Through this process, attainment of new identity and function is achieved by marked changes in cellular properties. Intrinsic cellular mechanisms governing stem cell differentiation remain largely unknown, in part because systematic forward genetic approaches to the problem have not been widely used1,2. Analysing genes required for germline stem cell differentiation in the Drosophila ovary,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
100
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(114 citation statements)
references
References 41 publications
9
100
1
1
Order By: Relevance
“…This embryonic lethality was a strict maternal effect dependent on the temperature of the mother, which rescue experiments suggest is caused by incompatibility between the nuclear Aatm V and mitochondrial tRNA tyr G:U alleles. The temperature-shift experiments suggested that early oogenesis is a temperature-sensitive period, which is known to be a crucial time for mitochondrial proliferation, transport and selection, and alleles of mitochondrial proteins can even influence early oocyte specification (Cox and Spradling, 2003;Hill et al, 2014;Hurd et al, 2016;Ma et al, 2014;Teixeira et al, 2015). Our analysis, however, did not reveal defects in mitochondrial number, transport or oocyte specification.…”
Section: Discussioncontrasting
confidence: 49%
“…This embryonic lethality was a strict maternal effect dependent on the temperature of the mother, which rescue experiments suggest is caused by incompatibility between the nuclear Aatm V and mitochondrial tRNA tyr G:U alleles. The temperature-shift experiments suggested that early oogenesis is a temperature-sensitive period, which is known to be a crucial time for mitochondrial proliferation, transport and selection, and alleles of mitochondrial proteins can even influence early oocyte specification (Cox and Spradling, 2003;Hill et al, 2014;Hurd et al, 2016;Ma et al, 2014;Teixeira et al, 2015). Our analysis, however, did not reveal defects in mitochondrial number, transport or oocyte specification.…”
Section: Discussioncontrasting
confidence: 49%
“…The dramatic reduction of Atpaf2 expression and deregulation of a large number of genes encoding ATP-binding proteins suggest that changes induced in embryonic germ cells are likely preserved in SG. Importantly, ATP synthase is a key protein required for germ cell differentiation (113) and expression changes in genes, encoding the subunits or assembly proteins of ATP synthase, such as Atpaf2 , could contribute to germ cell development. We also explored the idea that at least some changes in SG-derived lineages could originate in the cells that express POU5F1 as a key pluripotency factor.…”
Section: Discussionmentioning
confidence: 99%
“…These genes have never been identified in other stem cell-related RNAi screens. Interestingly, the loss of several subunits of mitochondrial ATP synthase leads to ovary differentiation defects (Teixeira et al, 2015). We did not identify any gene encoding mitochondrial ATP synthase subunits in our primary morphology screens.…”
Section: Non-cell Autonomous Effects Of Germ Cell Differentiationmentioning
confidence: 93%